Pain, Drug Leakage and Inflammation Associated with Intramuscular Injections of Magnesium Sulfate in Preeclamptic Women: A Descriptive Study. Issue 1 (January 2022) - Babu, Jayanthy J.; Venkadalakshmi, V.; Dhandapani, Manju; Chopra, Seema
Introduction: Magnesium sulfate (MgSO4 ) is the drug of choice for preventing and treating convulsions in severe preeclampsia and eclampsia by intramuscular (IM) and IV (IV) regimen. Repeated IM injections of MgSO4 at the same site causes pain, drug leakage, and injection site inflammation. To manage IM injection-related complications, it is important to have an estimation of these adverse effects. Objective: To evaluate the pain, drug leakage, and inflammation associated with IM injections of MgSO4 . Material and Methods: A longitudinal descriptive study was carried out in the labor room, PGIMER, Chandigarh. Thirty study participants diagnosed and admitted with preeclampsia were recruited by the total enumeration sampling technique. Each patient received eight IM injections of MgSO4 on the dorsogluteal site as prescribed by the obstetrician. Identification details, clinical, and biophysical characteristics were collected. The pain was assessed by a numerical rating scale (NRS). Sterile blotting paper was used to assess the drug leakage by measuring the wet area of the blotting paper and recording in cm 2 . A gridded transparent sheet was used for measuring inflammation. The area of the swelling marked and measured by placing the gridded transparent sheet over the swelling and recording in cm 2 . Results: Pain and drug leakage was significantly increased from the first injection to the eighth injection ( P < .05) and inflammation of 100.60 ± 21.23 (Right), 102.07 ± 21.23 (left) cm 2 recorded over the buttocks. Conclusion: Significant increase in pain, drug leakage, and inflammation were recorded during the IM administration of MgSO4 . For reducing the pain, drug leakage, and inflammation, nonpharmacological interventions and different techniques of IM injections are recommended.